Pengaruh Penggunaan Video Pembelajaran terhadap Hasil Belajar Siswa Kelas IV SDIT Permata Bangsa Tahun Pelajaran 2023/2024 - Septiana Sholikhah; Sri Suwartini; Isna Rahmawati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research is based on the background that learning activities at SDIT Permata Bangsa still use the lecture method, causing learning to become monotonous and the learning process in the classroom to be less interesting. This research aims to determine the effect of using learning videos on the learning outcomes of class IV students at SDIT Permata Bangsa. This research design uses a Quasi Experimental Design (Quasi Experimental) type Nonequivalent Control Group Design. The subjects of this research were class IV students at SDIT Permata Bangsa consisting of 28 students from class IV A totaling 14 students as the Experimental group and IV B totaling 14 students as the Control group. The data in this research were obtained through learning outcomes tests, namely pretest questions to test student learning outcomes before being given treatment and posttests, namely questions to test learning outcomes after being given treatment and documentation. The data analysis techniques used include normality, homogeneity and final analysis tests. Testing the final analysis or research hypothesis uses the paired sample t-test. The results of this research prove that the use of learning video media has a positive effect on improving the learning outcomes of class VI students at SDIT Permata Bangsa for the 2023/2024 academic year. This is shown from the results of the calculation of the paired sample t-test hypothesis test. The results obtained are tcount of 16,101 and ttable with df 20 is 2,086, meaning 16,101 > 2,086 (tcount is greater than ttable) so H1 is accepted and Ho is rejected. So it can be concluded that the use of learning video media influences the learning outcomes of class IV students at SDIT Permata Bangsa.